Analysis Of The Effect Of Banking Programs On Customer Loyalty At Pt Bank Maybank Indonesia Jakarta - Fahrur Rozi (Jurnal Indonesia Sosial Teknologi, 2023)
Bank Maybank Indonesia customers have a strong interest in depositing their funds into the bank. This research was conducted on customers of Bank Maybank Indonesia Jakarta branch. analyzing the relationship or influence of banking programs consisting of Maybank Gift (X1), Top Up Reward (X2), Cash Reward (X3), Maybank Interest-Free Mortgage (X4), Interest Bonus (X5), Arisan Retention (X6), and 100% Cash Back (X7) on Customer Loyalty (Y). This research uses multiple linear regression with data from the banking program. This study aimed to see the effect of banking programs on customer loyalty at PT Bank Maybank Indonesia Jakarta. this study uses multiple linear regression with primary data which is processed data that will be used as the results of this study. This study shows that the variables X1, X2, X5, and X7 have a significance value <0.05 which means that Maybank Gift (X1), Top Up Reward (X2), Interest Bonus (X5), and 100% Cash Back (X7) partially have a significant effect on the Customer Loyalty variable (Y).